Analysis of Socio-Economic Status, Morphology, and Dominant Factors of Personal Hygiene Behavior on the Incidence of Pediculosis Capitis at Orphanages in Palembang City, Indonesia - Jhon Riswanda; Chairil Anwar; Mohammad Zulkarnain; Rico Januar Sitorus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Pediculosis capitis affects all races and all social levels, but low socio-economic status is more affected by this disease. The mode of transmission can be direct (hair to hair) or through intermediaries such as hats, pillows, mattresses, combs, and veils. This study aims to analysis of socio-economic status, morphology, and dominant factors of personal hygiene behavior on the incidence of pediculosis capitis at Orphanages in Palembang City, Indonesia. The cross-sectional design is a sample of all orphanages in Palembang City. The results obtained were then analyzed by chi-square, logistics regression statistical test, and correspondence analysis. Morphology of pediculosis capitis female body length is 2461.70µm, male is 2596.90µm. Antenna shape are shorter and wider, abdomen curve is protruding. Crest of the paraterga plate is extends into the intersegmental membrane. Knowledge of respondents is not good and suffers from pediculosis capitis by 43 (74.1%), knowledge of respondents is good 52 (57.8%), attitude of respondents is negative and suffers from pediculosis capitis 27 (87.1%), positive attitude of the respondent suffered from pediculosis capitis 25 (42.4%), the respondent's actions were not good and suffered from pediculosis capitis 34 (75.6%), the respondent's action was good 18 (40%). The results of the logistic regression test: the most dominant factor is the attitude of the respondents (OR: 6.260 95% CI: 1.836-21.34). This research needs to be continued with individual characteristics in improving behavior in preventing pediculosis capitis.